Phase 3 Study of Vinflunine versus Docetaxel in Patients with Advanced Non-Small Cell Lung Cancer Previously Treated with a Platinum-Containing Regimen - Alexander, Walter (MD Conference Express, 2007)
This article discusses a phase 3 Study of vinflunine Versus docetaxel in patients with advanced non-small cell lung cancer (NSCLC) previously treated with a platinum-containing regimen, as well as results from the IRIS Study, and the use of surgery alone or surgery plus induction paclitaxel/carboplatin chemotherapy in early stage NSCLC.